The Resilience of Deficit Thinking - Curt Dudley-Marling (University of Windsor, 2015)
Deficit thinking, which situates school failure in the minds, bodies, communities and culture of students, dominates schooling practices in the US and Canada. From this perspective, the remedy to school failure is to "fix" students, their families, culture or language. Critics of deficit thinking point to systemic factors, especially diminished opportunities to learn, to explain high levels of school failure among poor students and students of color. Decades of fierce critique have failed to diminish the appeal of deficit thinking. This paper considers the resistance of deficit thinking to critique by examining the appeal of Ruby Payne's Culture of Poverty, a particularly egregious instantiation of deficit thinking that pathologizes the language and culture of people living in poverty. The paper then turns to more recent work by the author to counter deficit thinking by showing what happens when students in high-poverty schools are challenged by the kind of thoughtful, engaging, high-expectation curricula common in affluent, high-achieving schools and classrooms.